2019
DOI: 10.1007/s10637-019-00830-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1b study of a small molecule antagonist of human chemokine (C-C motif) receptor 2 (PF-04136309) in combination with nab-paclitaxel/gemcitabine in first-line treatment of metastatic pancreatic ductal adenocarcinoma

Abstract: Background In pancreatic ductal adenocarcinoma (PDAC), the chemokine (C-C motif) ligand 2 (CCL2)/chemokine (C-C motif) receptor 2 (CCR2) axis plays a key role in immunosuppressive properties of the tumor microenvironment, patient prognosis, and chemoresistance. This phase Ib study assessed the effects of the orally administered CCR2 inhibitor PF-04136309 in combination with nab-paclitaxel and gemcitabine in patients with previously untreated metastatic PDAC. Methods Patients received PF-04136309 twice daily (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 29 publications
2
94
1
Order By: Relevance
“…If replicated in larger, longitudinal samples, this signature might be helpful in identifying patients that should be fast-tracked into augmentation regimes-potentially a step toward overcoming the classic 'trial and error' approach in treating depression. In terms of novel targets, antagonists of P2RX7 72 , JAK 73 , CCR2 74 and FKBP5 16 are all novel antidepressant tools supported by our findings. Future studies will need to examine if these new treatments work, and whether responses to such new treatments can be improved by selecting patients with abnormal levels of relevant mRNAs 75 .…”
Section: Discussionsupporting
confidence: 77%
“…If replicated in larger, longitudinal samples, this signature might be helpful in identifying patients that should be fast-tracked into augmentation regimes-potentially a step toward overcoming the classic 'trial and error' approach in treating depression. In terms of novel targets, antagonists of P2RX7 72 , JAK 73 , CCR2 74 and FKBP5 16 are all novel antidepressant tools supported by our findings. Future studies will need to examine if these new treatments work, and whether responses to such new treatments can be improved by selecting patients with abnormal levels of relevant mRNAs 75 .…”
Section: Discussionsupporting
confidence: 77%
“…In the FOLFIRINOX group none objective response was observed [41]. On the contrary, the combination of PF-04136309 with paclitaxel and gemcitabine in metastatic pancreatic cancer displayed safety issues and had no therapeutic advantage with respect to the standard treatment [42]. The partial response to CCL2/CCR2 targeting strategies highlights that other chemokines, cytokines and growth factors contribute to the process, or may compensate the absence of CCL2/CCR2, with differences depending on the stage and the type of tumor, that hence need to be carefully evaluated for the development of effective strategies.…”
Section: Strategies Aimed At Inhibiting Tam Recruitmentmentioning
confidence: 95%
“…In a phase Ib clinical trial, a CCR2 antagonist (PF-04136309) was tested in combination with nab-paclitaxel plus gemcitabine in patients with pancreatic ductal adenocarcinoma. However, the results showed that PF-04136309 did not improve the efficacy compared to nab-paclitaxel plus gemcitabine [58].…”
Section: Blocking Of Mdsc Recruitmentmentioning
confidence: 88%